Looking to the North Sea: isotopic and osteological evidence for medieval diet, mobility, and health at Stoke Quay, Ipswich - Farber, ECE (2020)
The North Sea trading emporia of the early medieval period were instrumental in the redevelopment of overseas exchange networks in post-Roman Britain, southern Scandinavia, and Western Europe. These trade centres catalysed the process of urbanisation that intensified throughout the subsequent centuries, giving rise to the social and economic landscape of pre-modern England and Europe. Studying the emporia and their evolution into towns can provide insights into the factors that fuelled urbanisation, and can demonstrate the effect of this phenomenon on human diet, health, and mobility in the medieval period.